Online Dispute Resolution, Alternative Dispute Resolution Mechanisms and Artificial Intelligence for decongesting the administration of justice. - Bustamante Rúa, Mónica María; Ángel Muñoz, Santiago; Giraldo Aristizábal, Julián Andrés; Marín Tapiero, Jorge Iván (Law, State and Telecommunications Review, 2020)
Purpose ”“ This article seeks to analyze Online Dispute Resolution (ODR) in relation to Alternative Dispute Resolution Mechanisms, Artificial Intelligence and its effectiveness at decongesting the administration of justice. Methodology ”“ The research was qualitative analytical, is part of the so-called exploratory research, those that tend to determine trends, identify relationships between variables and serve for further research. For this purpose, was made a documentary analysis of articles published in legal journals and consulted through scientific databases, mostly virtual searches and findings, which allowed us to glimpse the legal institutions included in the Online Dispute Resolution and Alternative Dispute Resolution Mechanisms. Findings ”“ ODR has allowed the application of Alternative Dispute Resolution Mechanisms (ADR), such as mediation, conciliation, negotiation and amiable composition using virtual media that can even incorporate Artificial Intelligence (AI), to wit, the possibility that machines imitate human thinking to make decisions. It must respect the principles of transparency, equity, accountability and respect for offline general procedural guarantees, of which, celerity, economy, equality of arms and the pre-existence of procedural forms easily emerge in the online process, however, guarantees such as effective protection of rights, impartiality, independence, immediacy and publicity could be blurred.